Analysis of Operational Management Implementation at Kalbe Farma Tbk - Devina Wistiasari; Maria Yosefina Meinadia Sekar Kinanti Aswirawan; Rizki Fadhel Dwipananda (Neo Journal of economy and social humanities, 2025)
This research analyzes the implementation of operational management in PT Kalbe Farma Tbk one of a leading pharmaceutical industry in Indonesia through the strategic location selection. Using a qualitative description approach and secondary data, this study provides a description of the Kalbe Farma’s holistic operational practice, such as integration of supply chain, human resources development, technologies. The company excels in strategic location planning, locating production and distribution centers near transportation nodes and population centers with strong market concentrations to enhance efficiency and minimize the cost of logistics. Yet, the steep rise in land prices and congestion in infrastructure etc, continue to remain as challenges. Kalbe tackles these by using digital inventory systems and strengthening partnerships with the public sector. The results illustrate that there are five key success factors for location strategy: market access, supply chain management, qualified labor force, technological assimilation, and environmentalism. Secondly, in its corporate transformation, Kalbe Farma uses a hub-and-spoke approach to optimize service location and national distribution radii. The strategic operation management such as location planning of Kalbe Farma is able to help to keep the competitive position and satisfy their customer throughout Indonesia. The following findings would provide a benchmark, which would then be of use to other manufacturing and distribution-based companies on how to shape their special rational strategies.